2012
DOI: 10.1089/mdr.2011.0019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fluoroquinolone Resistance Mechanisms inPseudomonas aeruginosaMultidrug Resistance Clinical Isolates

Abstract: Efflux transporters have a considerable role in the multidrug resistance (MDR) of Pseudomonas aeruginosa, an important nosocomial pathogen. In this study, 45 P. aeruginosa clinical strains, with an MDR phenotype, have been isolated in a hospital of Northern Italy and characterized to identify the mechanisms responsible for their fluoroquinolone (FQ) resistance. These isolates were analyzed for clonal similarity, mutations in genes encoding the FQ targets, overexpression of specific Resistance Nodulation-cell D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
7
23
0
Order By: Relevance
“…We examined the genome data for mutations that accumulated independently in the different sublineages (see Table S1 in the supplemental material). As anticipated, such parallel evolution was observed in genes known to be involved in antibiotic resistance and included mutations in DNA gyrases gyrA (clusters B and C), gyrB (clusters A and C), and fusA1 (clusters B and C), encoding elongation factor G (Table S1) (26, 27). Unexpectedly, no other examples of parallel genomic evolution were found, which suggests that the three sublineages exist in separate niches, each with different selective conditions by which evolution is directed.…”
Section: Resultsmentioning
confidence: 54%
“…We examined the genome data for mutations that accumulated independently in the different sublineages (see Table S1 in the supplemental material). As anticipated, such parallel evolution was observed in genes known to be involved in antibiotic resistance and included mutations in DNA gyrases gyrA (clusters B and C), gyrB (clusters A and C), and fusA1 (clusters B and C), encoding elongation factor G (Table S1) (26, 27). Unexpectedly, no other examples of parallel genomic evolution were found, which suggests that the three sublineages exist in separate niches, each with different selective conditions by which evolution is directed.…”
Section: Resultsmentioning
confidence: 54%
“…The constitutive overproduction of the proteins MexXY is generally associated with a 2-to 16-fold increase in the MICs of pump substrates (18,19). In addition to CF and non-CF clinical MexXY-OprM-overproducing strains found to harbor mutations inactivating the gene mexZ (e.g., indels, premature stop codons) or its product, MexZ (e.g., amino acid substitutions), isolates harboring intact (wild-type) mexZ genes have repeatedly been reported (19)(20)(21)(22)(23)(24)(25) but have rarely been characterized (26). The observation that MexXY-OprM-upregulated mutants with defective protein synthesis can be selected in vitro on aminoglycoside (7,26,27) or a peptide deformylase inhibitor (28) suggested that such mutants, called agrW1, to differentiate them from mexZ mutants (dubbed agrZ), might be hypovirulent and thus poorly relevant in the clinic setting because of impaired fitness.…”
mentioning
confidence: 99%
“…For example, ten of the genes (gyrA, gyrB, mexA, mexB, mexR, mexS, mexZ, nalD, nfxB and oprD) have been shown to be involved in resistance against a range of antibiotics 27,[30][31][32][33] , such as β-lactams, quinolones, chloramphenicol, macrolides, aminoglycosides and penicillins, and eight of the genes (bifA, lasR, morA, phaF, rbdA, retS, wspA and wspE) are involved in regulation of biofilm formation [34][35][36][37][38][39][40] .…”
Section: Function Of Pathoadaptive Genesmentioning
confidence: 99%